2010
DOI: 10.1080/00223891.2010.497393
|View full text |Cite
|
Sign up to set email alerts
|

Reference Group Effects in the Measurement of Personality and Attitudes

Abstract: Reference-group effects (discovered in cross-cultural settings) occur when responses to self-report items are based not on respondents' absolute level of a construct but rather on their level relative to a salient comparison group. In this article, we examine the impact of reference-group effects on the assessment of self-reported personality and attitudes. Two studies illustrate that a reference-group effect can be induced by small changes to instruction sets, changes that mirror the instruction sets of commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…This result may explain why, in apparent conflict with a cognitive model of personality judgments, 63 specifying reference groups reduced predictive validity in a study of conscientiousness. 41 If most people do not naturally tend to compare themselves to a reference group, they may do worse when required to do so. Much of the literature has focused on finding out whether questions could be improved, by specifying their frame of reference, 41,42 reference groups, 63,64 examples, 40 or specific behaviours, 65,66 or by generally reducing temporary, fluctuating influences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result may explain why, in apparent conflict with a cognitive model of personality judgments, 63 specifying reference groups reduced predictive validity in a study of conscientiousness. 41 If most people do not naturally tend to compare themselves to a reference group, they may do worse when required to do so. Much of the literature has focused on finding out whether questions could be improved, by specifying their frame of reference, 41,42 reference groups, 63,64 examples, 40 or specific behaviours, 65,66 or by generally reducing temporary, fluctuating influences.…”
Section: Discussionmentioning
confidence: 99%
“…41 If most people do not naturally tend to compare themselves to a reference group, they may do worse when required to do so. Much of the literature has focused on finding out whether questions could be improved, by specifying their frame of reference, 41,42 reference groups, 63,64 examples, 40 or specific behaviours, 65,66 or by generally reducing temporary, fluctuating influences. 27,28 In risk preference research, Blais and Weber 51 attempted to remove any part played by differences in risk perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To more affluent raters, they seem less competent, because their wealth no longer needs to be explained by the target’s traits. Existing research suggests that raters use the ingroup as a comparison standard in the judgment of personality (Credé, Bashshur, & Niehorster, 2010), even in the case of minimal groups (e.g., Sherif & Sherif, 1953). As such, outgroup members were generally rated in contrast to the ingroup across personality facets in the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore , Credé, Bashshur, and Niehorster (2010) demonstrated that measures instructing participants to use specific reference groups generally lead to decreased criterion validity of those scales. In our study, the Goldberg adjective measures of Neuroticism and Extraversion were the only measures to employ such an instruction set.…”
Section: Basic Implications Of Our Findingsmentioning
confidence: 99%